PROPHET IDRĪS AS THE INVENTOR OF ISLAMIC ASTRONOMY FROM THE BIBLE AND AL-QUR’AN PERSPECTIVES - Faza, Ricka Ulfatul; Yaqin, Ahmad Ainul (Fakultas Syari'ah dan Hukum UIN Walisongo, 2024)
Astronomy is the oldest science discovered. Therefore, the discussion of who the first inventor of astronomy was is interesting to explore. Some literature states that the Prophet Idrīs was the first person to know astronomy. However, there is also an opinion that the Prophet Unusy had known astronomy long before the Prophet Idrīs was born. To discover who invented astronomy, we need to trace who the Prophet Idrīs was when viewed from the perspective of the Bible (Old Testament and New Testament) and the Qur'an. Through a historical approach and analytical descriptive method, this article explains the results of a study related to the biography of the Prophet Idrīs and his genealogy according to the Bible and the Qur'an, as well as several opinions of astronomy experts who confirm the Prophet Idrīs as the inventor of astronomy.